Optimasi Keamanan Jaringan dengan Metode Sentralisasi Koneksi VPN Berbasis Zerotier pada Industri Soho - Nasrullah Syamil Salahudin; Yuma Akbar (Penerbit Jurnal Indonesia, 2025)
Network security plays a crucial role in supporting productivity and ensuring operational continuity within Small Office/Home Office (SOHO) environments. However, limitations in infrastructure and technical resources often hinder the implementation of reliable and efficient security solutions. This study aims to optimize network security through a centralized VPN connection approach using ZeroTier technology. ZeroTier is a peer-to-peer-based virtual network solution that supports end-to-end encryption using the AES-256-GCM protocol and public key authentication based on Curve25519. It enables secure connections between computers within a virtual local network, even if they are physically located in different places. This research employs an experimental methodology by comparing two scenarios: a SOHO network without VPN and a SOHO network with centralized VPN connectivity using ZeroTier. The evaluation focuses on security parameters (encryption, authentication, and secure routing), network performance (latency and throughput), and ease of implementation. The results show that implementing ZeroTier significantly enhances data communication security without requiring additional physical infrastructure. Furthermore, the centralized connection scheme offers centralized traffic control, simplifies access management, and reduces potential vulnerabilities from uncontrolled peer-to-peer connections. In conclusion, the application of centralized VPN connections using ZeroTier proves effective in optimizing network security for SOHO environments through a lightweight, efficient, and easy-to-implement approach.